REVENGE IN WILLIAM SHAKESPEARE'S HAMLET: A PSYCHOANALYTIC APPROACH - SUHARTO , APRILIA TUTUT (2010)
The major problem of this study is how revenge is reflected in the major character's personality. The aim of this study is to analyze William Shakespeare's Hamleton the structural elements and the development of personality of the major character based on Psychoanalytic Approach. This study focuses on the major character, namely Hamlet. The benefit of this research is to give additional information which can be used by the other literature researchers who are interested in analyzing this play. This study uses two data sources, namely primary and secondary data source. The primary data source is the play script itself, while the secondary data are taken from some information needed. The method of data collection is qualitative method. Based on the analysis, the outcome of this study shows that the problem of major character encounters causes the conflict of his mental condition. Then, it develops to become anxiety and influences him to takea revenge for the death of his father. Finally, the plan to kill his uncle becomes reality; he kills his uncle and also his friend. He is also killed in the competition by his own friend.